44 Assessing a novel jump-landing protocol for dynamic stability in high-level athletes. (12th October 2015) - Liu, K; Dierkes, C; Blair, L
Abstract : Background: Current jump-landing protocols have identified impairments in dynamic stability in recreational individuals, but have not elicited differences in high-level athletes. Objective: To develop a new jump-landing protocol to identify differences in dynamic stability in high-level athletes. Design: Case-control study. Setting: Movement Analysis Lab. Participants: 61 Division-I collegiate athletes (32 females, 29 males; age = 19.9 ± 1.2 years; height = 76.6 ± 9.5 cm; body mass = 74.1 ± 0.8 kg) were separated into healthy, coper, and unstable groups based on the Cumberland Ankle Instability Tool and their ankle injury history. Interventions: Two jumping tasks from the forward and lateral directions were executed barefooted onto the force plate. For the forward jump, participants took two preparatory steps, jumped to 50% of their maximum vertical jump, and landed single-legged on the force plate. For the lateral jump, participants took two side-shuffle steps and jumped to 50% of their maximum vertical jump, again landing single-legged on the force plate. All participants were instructed to stabilise as quickly as possible and remain motionless for 5 s. Three trials were collected for each jump in a randomised order. Main outcome measurements: ROC curves were utilised to compare the accuracy of this jump landing protocol to differentiate time-to-stability (TTS) measures among groups. Results: Asymptotic significance were detected between the healthy and unstable groups (forward: p = 0.001, AUC: 0.800; lateral: p = 0.011, AUC: 0.739), as well as the coper and unstable groups (forward: p = 0.013, AUC: 0.732; lateral: p = 0.015, AUC: 0.728). The healthy and coper groups had similar TTS scores (forward: p = 0.328, AUC: 0.407; lateral: p = 0.907, AUC: 0.489). Conclusions: This jump-landing protocol accurately detects differences in TTS among the healthy, coper, and unstable groups of high-level athletes. Previous jump-landing protocols identified poor stability measures in the unstable group of recreational individuals, but not of high-level athletes. Perhaps, this new jump-landing protocol better taxes the sensorimotor system of high-level athletes, giving clinicians the ability to identify those at risk of injury and implement interventions to reduce these risks.